A retrospective observational study of the impact of Tigecycline in treating multidrug resistant pneumonia - Paul, John; Paul, Cherish (International Journal of Clinical Trials, 2017)
Background: Few antimicrobials are currently active to treat extensively drug resistant (XDR) gram-negative bacilli infections. This represents a serious global public health concern. Critically ill patients face the brunt of majority of these infections. Tigecycline has coverage for a majority of these XDR infections (with the exception of Pseudomonas aeruginosa), but is not currently approved for hospital-acquired pneumonia. Nevertheless it is being commonly used for this indication though many meta-analysis have suggested an increased risk of death in patients receiving this antibiotic. Methods: In this retrospective analysis we compared the mortality rates between a Tigecycline based and a non Tigecycline based therapy for XDR infections in the critically ill over a period of 12 months. A total of 93 patients were included in the study. Results: Tigecycline group had significantly increased risk for in hospital mortality with an odds ratio of 6.0 and 95% CI of 1.37 to 26.12 with a p value of 0.01. But such a difference was not evident in 14 day mortality. Conclusions: Initiation of Tigecycline for multidrug resistant, pneumonia needs to be re-thought. Only a small percentage of patients with pneumonia with in-vitro sensitivity having low minimum inhibitory concentration (MIC) would benefit from the drug. Even in this group the risk of increased mortality needs to be carefully considered before Initiation of therapy.